“Hei de amar-te até morrer!" notes about the brazilian genre "modinha" - Dietrich, Peter; Discini, Norma; Lopes, Ivã Carlos (Laboratório Editorial FCL-UNESP, 2008)
On the basis of some contributions to musical semiotics by Luiz Tatit, we present an analysis of the XIXth century Brazilian song named "Hei de amar-te até morrer!". We focus on the relation between melody and lyrics, assuming this to be the source for the production of meaning in musical language. Our analysis' aim is to demonstrate that what is verbally said is also musically done in the song.